D701N mutation in the PB2 protein contributes to the pathogenicity of H5N1 avian influenza viruses but not transmissibility in guinea pigs - Jiao, Peirong; Wei, Liangmeng; Song, Yafen; Cui, Jin; Song, Hui; Cao, Lan; Yuan, Runyu; Luo, Kaijian; Liao, Ming (Frontiers in Microbiology, 2014)
H5N1 highly pathogenic avian influenza virus (HPAIV) of clade 2.3.2 has been circulating in waterfowl in Southern China since 2003. Our previous studies showed that certain H5N1 HPAIV isolates within clade 2.3.2 from Southern China had high pathogenicity in different birds. Guinea pigs have been successfully used as models to evaluate the transmissibility of AIVs and other species of influenza viruses in mammalian hosts. However, few studies have reported pathogenicity and transmissibility of H5N1 HPAIVs of this clade in guinea pigs. In this study, we selected an H5N1 HPAIV isolate, A/duck/Guangdong/357/2008, to investigate the pathogenicity and transmissibility of the virus in guinea pigs. The virus had high pathogenicity in mice; additionally, it only replicated in some tissues of the guinea pigs without production of clinical signs, but was transmissible among guinea pigs. Interestingly, virus isolates from co-caged guinea pigs had the D701N mutation in the PB2 protein. These mutant viruses showed higher pathogenicity in mice and higher replication capability in guinea pigs but did not demonstrate enhanced the transmissibility among guinea pigs. These findings indicate the transmission of the H5N1 virus between mammals could induce virus mutations, and the mutant viruses might have higher pathogenicity in mammals without higher transmissibility. Therefore, the continued evaluation of the pathogenicity and transmissibility of avian influenza virus (AIVs) in mammals is critical to the understanding of the evolutionary characteristics of AIVs and the emergence of potential pandemic strains.